The inverse function of d(x) = 2x - 4 is y = (x + 4)/2.
The inverse function of d(x) = 2x - 4 can be found by following a step-by-step process. Let y = 2x - 4 be the original function. To find the inverse function, swap x and y in the equation and solve for y. This will give us the inverse function as y = (x + 4)/2.
Answer:
(x) =
Step-by-step explanation:
let d(x) = y and rearrange making x the subject, that is
2x - 4 = y ( add 4 to both sides )
2x = y + 4 ( divide both sides by 2 )
x =
Change y back into terms of x, so
(x ) =
5.8m questions
7.5m answers